2022
DOI: 10.3389/fvets.2021.802570
|View full text |Cite
|
Sign up to set email alerts
|

Coinfections and Phenotypic Antimicrobial Resistance in Actinobacillus pleuropneumoniae Strains Isolated From Diseased Swine in North Western Germany—Temporal Patterns in Samples From Routine Laboratory Practice From 2006 to 2020

Abstract: Actinobacillus pleuropneumoniae (APP) is one major bacterial porcine respiratory tract pathogen causing disease outbreaks worldwide, although effective commercial vaccines are available. Due to frequent failure of this preventive measure, treatment with antimicrobials is indispensable to prevent animal losses within an outbreak situation. To preserve the effectivity of antimicrobial substances to fight APP should therefore be the primary aim of any interventions. In this study, the temporal development of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A previous study also showed that A. pleuropneumoniae -infected pigs were usually coinfected with porcine circovirus 2 (PCV2, 56%), Streptococcus suis (24.8%), or the porcine reproductive and respiratory syndrome virus (PRRSV, 23.3%) (Hennig-Pauka et al. 2021 ). The increased frequency of A. pleuropneumoniae coincided with the PCV2 and PRRSV was found in the Hungarian porcine industry (Kardos et al.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study also showed that A. pleuropneumoniae -infected pigs were usually coinfected with porcine circovirus 2 (PCV2, 56%), Streptococcus suis (24.8%), or the porcine reproductive and respiratory syndrome virus (PRRSV, 23.3%) (Hennig-Pauka et al. 2021 ). The increased frequency of A. pleuropneumoniae coincided with the PCV2 and PRRSV was found in the Hungarian porcine industry (Kardos et al.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, antibiotic resistance poses a global threat pertaining to lung infections, so novel methods to screen effective anti-bacterial drugs with novel mechanisms are needed [4]. APP that resists one and multiple antibiotics have been found in pig farms though APP is not a human pathogen [5,8]. Even in cases of no antibiotic resistance and residue, vaccines for APP are sometimes ineffective because of a lack of appropriate antigens, low cross-reactivity, and immune escape.…”
Section: Introductionmentioning
confidence: 99%
“…However, excessive application of antimicrobial agents has led to the emergence of multidrug resistant (MDR) bacteria ( 7 , 8 ). The common solutions to address MDR include the development of new drugs, reformation of susceptibility breakpoints, drug combinations, and optimization of dosage regimens.…”
Section: Introductionmentioning
confidence: 99%